Evaluation of senescence, proliferation, and cell death mechanisms in the liver of pregnant rats exposed to a high-fat diet (Research, Society and Development, 2025)
This study aimed to evaluate whether the processes of proliferation, senescence, and cell death are involved in the exacerbation of liver size increase at the end of pregnancy in rats subjected to a high-fat diet. Sprague Dawley rats (n=9/group), which consumed a standard diet (control) and a high-fat diet (HFD) from weaning to the end of pregnancy. These rats were mated, consumed the diet, and at the end of 21 days of pregnancy, liver samples were collected for evaluation of immunostaining for Ki-67 (cell proliferation), cleaved caspase-3 (cell death) and Sudan black (cellular senescence). Student's t-test and Fisher’s Exact test were used for comparison, considering p